Developing Entrepreneurship in Islamic Economics at Ipah Pusakajaya Wholesale Store - Iah Saniah; Lutfi Maulana; Nurlailiyah Aidatus Sholihah (Journal of Business Improvement, 2024)
This paper aims to explain how to build entrepreneurship in the perspective of Sharia economics at Toko Ipah Grosir Pusakajaya. The method used in this writing is a qualitative research approach. The primary data sources used are from literature studies related to entrepreneurship, and secondary data interview searches of previous articles related to entrepreneurship information. The collection technique is in the form of the results of searching journals for research articles related to entrepreneurship. Data analysis techniques are descriptive. Building an entrepreneurship is an obligation that must be done by someone. The cause of a person's obligation to do entrepreneurship is to be able to help fellow humans in building a low economy. The nature of discipline, honesty, realism, and productivity, is one of the improvements of entrepreneurship in building good character. The purpose of entrepreneurship to be balanced between the world, and the hereafter, is to pay attention to gratitude for the blessings given in a business, provide benefits for fellow humans, and not harm others. That way an entrepreneur can be said to be successful if it can provide benefits both for the world and the hereafter